Transformational Leadership, Organizational Culture, Change Management, and Employee Engagement - Widjajakusuma, Kresna; Anindita, Rina (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the influence of transformational leadership, organizational culture, change management, and employee engagement on readiness to change within the Indonesian banking sector. It highlights how leadership behavior and cultural alignment shape employees’ willingness and preparedness to adapt to organizational transformation. Research Methodology: Data were collected from 201 permanent employees of Tier-4 banks (Bank Mandiri, BRI, BNI, and BCA) through online questionnaires using a quantitative cross-sectional design. Analysis was conducted using partial least squares structural equation modeling (PLS-SEM) to test the relationships among the variables. Results: The structural model indicated that transformational leadership significantly predicted organizational culture (? = 0.625; t = 15.332; p < 0.001) and change management (? = 0.318; t = 4.270; p < 0.001). Change management significantly increased employee engagement (? = 0.535; t = 9.250; p < 0.001), and employee engagement, in turn, predicted readiness to change (? = 0.601; t = 11.758; p < 0.001). Conclusions: The results confirm that transformational leadership, effective change management, and strong organizational culture collectively foster employee engagement and readiness for change. These factors are crucial for maintaining the adaptability and competitiveness of Indonesia’s banking industry. Limitations: This study focuses on Tier-4 banks, limiting its generalizability to smaller institutions. Future studies could include broader sectors and longitudinal data. Contributions: This research contributes empirical evidence to the human resource management literature by identifying engagement as a key mediating factor between leadership and readiness to change, providing strategic insights for organizational transformation.